Thyroid hormones in relation to toxic metal exposure in pregnancy, and potential interactions with iodine and selenium. (December 2021) - Gustin, Klara; Barman, Malin; Skröder, Helena; Jacobsson, Bo; Sandin, Anna; Sandberg, Ann-Sofie; Wold, Agnes E.; Vahter, Marie; Kippler, Maria
Abstract: Background: Several endocrine-disrupting metals may affect thyroid function, but the few available studies of exposure during pregnancy and thyroid hormones are inconclusive. Objective: To explore if environmental exposure to cadmium (Cd), lead (Pb), and methylmercury (MeHg) impacts thyroid function in pregnancy, and interacts with iodine and selenium status. Methods: Women in a Swedish birth cohort provided blood and urine samples in early third trimester. Concentrations of erythrocyte Cd, Pb, and Hg (n = 544), urinary Cd and iodine (n = 542) and plasma selenium (n = 548) were measured using inductively coupled plasma-mass spectrometry. Free and total thyroxine (fT4, tT4) and triiodothyronine (fT3, tT3), and thyroid stimulating hormone (TSH), were measured in plasma (n = 548) with electrochemiluminescence immunoassays. Metal-hormone associations were assessed in regression models, and metal mixture effects and metal-nutrient interactions were explored in Bayesian kernel machine regression (BKMR). Results: In multivariable-adjusted regression models, a doubling of urinary Cd was associated with a mean increase in tT4 of 2.7 nmol/L (95% CI: 0.78, 4.6), and in fT3 and tT3 of 0.06 pmol/L (0.02, 0.10) and 0.09 nmol/L (0.05, 0.13), respectively. A doubling of urinary Cd was associated with a −0.002 (−0.003, −0.001) and −0.03 (−0.05, −0.02) decrease in the fT4:tT4 and fT3:tT3 ratio, respectively. A doubling of erythrocyte Hg (>1 µg/kg) was associated with a decrease in fT3 and tT3 by −0.11 pmol/L (−0.16, −0.05) and −0.11 nmol/L (−0.16, −0.06), respectively, and a −0.013 (−0.02, −0.01) decrease in the fT3:fT4 ratio. BKMR did not indicate any mixture effect of toxic metals or interactions between metals and iodine or selenium in relation to the hormones. Conclusion: Our findings suggest that exposure to Cd and Hg, at levels globally prevalent through the diet, may affect thyroid function during pregnancy, independently of iodine and selenium levels. Further studies on potential implications for maternal and child health are warranted.